Insulin resistance is associated with all chronic complications in type 1 diabetes. (28th April 2015) - Pop, Andrei; Clenciu, Diana; Anghel, Monica; Radu, Stefania; Socea, Bogdan; Mota, Eugen; Mota, Maria; Panduru, Nicolae M.
Abstract: Background: Insulin resistance (IR) is present in type 1 diabetes mellitus (T1DM) and is suggested to be related to chronic diabetic complications. The primary aim of our study was to assess IR in T1DM patients with and without chronic complications. A secondary aim was to evaluate the possible association between IR and chronic diabetic complications. Methods: This cross‐sectional study enrolled 272 patients with T1DM. Insulin resistance was quantified using the estimated glucose disposal rate (eGDR). Associations between eGDR and each diabetes complication were first evaluated using binary logistic regression, then multiparametric logistic regression with stepwise selection of covariates. The discriminative value of eGDR was assessed by receiver operating characteristic (ROC) curve analysis. Results: Estimated GDR was lower in patients with chronic diabetic complications (6.1 vs 6.9 mg/kg per min [ P = 0.02] for retinopathy; 6.3 vs 7.3 mg/kg per min [ P < 0.01] for nephropathy; 6.5 vs 7.6 mg/kg per min [ P < 0.01] for neuropathy; and 5.2 vs 7.5 mg/kg per min [ P < 0.01] for cardiovascular complications). In univariate analysis eGDR was associated all diabetic complications. These associations remained significant after adjustment for different variables in the final regression models. In addition, eGDR was a good discriminator for each diabetic complication, with an area under the curve between 0.609 and 0.759. Conclusions: Patients with chronic diabetic complications are more insulin resistant than those without complications. Moreover, IR was independently associated with the presence of each chronic diabetic complication, and seems to be a good discriminator for them all.